Petrogenesis of low-Ti and high-Ti magmatic rocks of the Jurassic Ferrar Large Igneous Province, Antarctica - Hanemann, Ricarda (2007)
This study of Ferrar magmatic rocks from northern Victorialand and George V Land, Antarctica, is directed towards a better understanding of the petrogenesis of the two compositionally distinct magma series present within the Mid-Jurassic Ferrar Large Igneous Province: a low-Ti series (LTS: TiO2 ~ 0.4 – 1.2 wt%) and a high-Ti series (HTS: TiO2 ~ 1.7 – 2.1 wt%). On the basis of their mineral and whole-rock chemical compositions (including rare earth elements and platinum-group elements) the differentiation history, the melt generation and magma source characteristics are evaluated. For both magma series, an identical primary magma is deduced that has been generated by high-degree partial melting of a single, refractory subcontinental lithospheric magma source. A polybaric differentiation model is developed suggesting that the two magma series experienced pre-emplacement differentiation within independent temporary magma reservoirs at different crustal depths and hence under different prevailing conditions. Based on this model, the influence of changing redox conditions and water activities on the Ferrar magma evolution is examined by equilibrium crystallisation experiments performed in internally heated pressure vessels. The comparison of the experimental results with the compositional differences analysed in the natural low-Ti and high-Ti rocks indicates that prior to final magma emplacement at upper crustal levels the HTS magma differentiated under lower pressure, lower water activity and lower oxygen fugacity than the LTS magma.